Tackling the primary healthcare workforce crisis: time to talk about health systems and governance—a comparative assessment of nine countries in the WHO European region - Ellen Kuhlmann; Michelle Falkenbach; Monica Georgina Brînzac; Tiago Correia; Maria Panagioti; Bernd Rechel; Anna Sagan; Milena Santric-Milicevic; Marius-Ionuț Ungureanu; Iris Wallenburg; Viola Burau (Human Resources for Health)
Abstract Background Primary healthcare has emerged as a powerful global concept, but little attention has been directed towards the pivotal role of the healthcare workforce and the diverse institutional setting in which they work. This study aims to bridge the gap between the primary healthcare policy and the ongoing healthcare workforce crisis debate by introducing a health system and governance approach to identify capacities that may help respond effectively to the HCWF crisis in health system contexts. Methods A qualitative comparative methodology was employed, and a rapid assessment of the primary healthcare workforce was conducted across nine countries: Denmark, Germany, Kazakhstan, Netherlands, Portugal, Romania, Serbia, Switzerland, and the United Kingdom/ England. Results Our findings reveal both convergence and pronounced diversity across the healthcare systems, with none fully aligning with the ideal attributes of primary healthcare suggested by WHO. However, across all categories, Denmark, the Netherlands, and to a lesser extent Kazakhstan, depict closer alignment to this model than the other countries. Workforce composition and skill-mix vary strongly, while disparities persist in education and data availability, particularly within Social Health Insurance systems. Policy responses and interventions span governance, organisational, and professional realms, although with weaknesses in the implementation of policies and a systematic lack of data and evaluation. Conclusions Aligning primary healthcare and workforce considerations within the broader health system context may help move the debate forward and build governance capacities to improve resilience in both areas.